2014
DOI: 10.1074/jbc.m113.483115
|View full text |Cite|
|
Sign up to set email alerts
|

Myostatin Induces DNA Damage in Skeletal Muscle of Streptozotocin-induced Type 1 Diabetic Mice

Abstract: Background: Uncontrolled type 1 diabetes leads to DNA damage and skeletal muscle atrophy. Results: STZ-induced Foxa2 up-regulates Mstn leading to DNA damage via p63/REDD1 pathway in skeletal muscle. Conclusion: Mstn is a target of Foxa2. Blocking Mstn can attenuate DNA damage in the diabetic muscle. Significance: The findings reveal a mechanism of induction of Mstn and DNA damage during diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In murine study, it was reported that DNA damage in muscle occurs prior to muscle degeneration (Sandri et al 1995). And decreased DNA damage accumulation in myostatin knockout mice showed decreased muscle degeneration (Sriram et al 2014). Therefore, our data b Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In murine study, it was reported that DNA damage in muscle occurs prior to muscle degeneration (Sandri et al 1995). And decreased DNA damage accumulation in myostatin knockout mice showed decreased muscle degeneration (Sriram et al 2014). Therefore, our data b Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The changed muscle lipid metabolism has its influence on glucose metabolism and could be at the starting point of muscle insulin resistance. For this, there are currently a few hypotheses [49,[54][55][56][57][58], which go beyond the scope of this review.…”
Section: Pathophysiologic Mechanismsmentioning
confidence: 99%
“…a) through binding to a sterol regulatory element present in the myostatin promoter to promote insulin resistance . In addition, myostatin transcription is upregulated in skeletal muscle of streptozotocin‐induced type 1 diabetic mice through the action of the Foxa2 transcription factor, which is activated due to reduced insulin signaling in type 1 diabetic muscle .…”
Section: Regulation Of Myostatinmentioning
confidence: 99%